Mesomechanical constitutive modeling - Kafka, Vratislav (Series on advances in mathematics for applied sciences, 2001)
This monograph presents an original concept of constitutive modeling of a wide variety of materials that are microscopically heterogeneous and macroscopically homogeneous. From one point of view it is a generalization of the fictitious classical 'series' and 'parallel' models; the author's model covers as special cases real structures of two-phase materials with inclusions in a matrix, or with both substructures being continuous or discontinuous. From another point of view it is a special case of a model with tensorial internal variables. Concrete structures are characterized by specific structural parameters that can be determined by simple macroscopic tests. Examples of applications to plasticity, reology, shape memory and continuum damage, as well as to metallic polycrystalline materials and concrete and fiber-reinforced materials, are demonstrated.